Microplankton composition, production and upwelling dynamics in Sagres (SW Portugal) during the summer of 2001 - Loureiro, S. (2018)
Microplankton community, production, and respiration were studied alongside physical and chemical conditions at Sagres (SW Portugal) during the upwelling season, from May to September 2001. The sampling station was 5 km east of the upwelling centre off Cabo S. Vicente, and 2 km west of an offshore installation for bivalve aquaculture. Three major periods were distinguished according to sea surface temperature (SST): period I (Pl; May and June), characterised by high temperature values (17.0 +/- 1.8 degrees C); period 2 (P2; July), characterised by lower temperatures (14.6 +/- 0.3 degrees C), identified as an upwelling-blooming stage; and period 3 (P3; August), characterised by a high temperature pattern (16.25 +/- 1.14 degrees C). Chaetoceros spp., Thalassiosira spp., Lauderia spp., Detonula spp. and Pseudo-nitzschia spp. were the major taxa contributing to the dissimilarities between P2 (July) and the other periods. In July (P2), the average gross production (GP; 52.5 +/- 12.3 mu M O-2 d(-1)) and net community production (NCP; 46.9 +/- 15.3 mu M O-2 d(-1)) peaked with the maximal concentrations of diatom-chl a. Dark community respiration (DCR) remained low and more constant throughout (4.6 +/- 3.6 mu M O-2 d(-1)). The plankton assemblage was dominated by diatoms throughout the survey. Physical events were the primary factors determining the microplankton structure and distribution at this location.